News for assimilation or integration? Examining the functions of news in shaping acculturation experiences of immigrants in the Netherlands and Spain - Alencar, Amanda and Deuze, Mark (European Journal of Communication, 2017)
This study investigates the functions of news media in shaping acculturation experiences of new economic and refugee immigrants in the Netherlands and Spain. Focus group data revealed that consumption of host country news media was mainly connected to immigrants’ deliberate strategies to assimilate the culture, politics and language of the host society, while exposure to transnational news was viewed in terms of strategies of integration in both countries. We also observed that participants’ educational background and language skills combined with their perceptions of the host country’s news have an impact on the use they make of news for assimilating and/or integrating into the host society. Finally, important sociopolitical conditions of the context influenced the ways participants use the news media in their process of acculturation.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMjY3MzIzMTE3Njg5OTkz